Fostering Resources for Undergraduate Research at the City University of New York. Issue 169 (March 2015) - MacLachlan, Effie S.; Caplan, Avrom J.
Abstract : Securing funding for undergraduate research activities is critical to a vibrant program. Strategies for obtaining funding are described in this chapter.